2017
DOI: 10.1016/j.bjorl.2016.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic repair of cerebrospinal fluid rhinorrhea

Abstract: Endoscopic diagnosis and repair of cerebrospinal fluid fistulas using fluorescein intrathecally has high success rate and low complication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Kljajić et al [11] reported that male patients outnumbered female ones in the group of traumatic CSF leaks, while most of the patients with spontaneous CSF leaks were female ones. Our study confirms that spontaneous Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Kljajić et al [11] reported that male patients outnumbered female ones in the group of traumatic CSF leaks, while most of the patients with spontaneous CSF leaks were female ones. Our study confirms that spontaneous Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The extended skull base exposure with ESBS increases the incidence of CSF leak to 7% [29]. Common sites for anterior skull base defects are in the ethmoid and sphenoid sinuses [30,31]. Recognising skull base damage and subsequent CSF leak during initial FESS allows concurrent repair; missed skull base damage may require additional surgical reparative procedures, adding to the patient's morbidity and inpatient stay [32].…”
Section: Cerebrospinal Fluid Rhinorrhoeamentioning
confidence: 99%
“…MRI and MR cisternography are useful in situations of multiple bony defects, or where the site of defect cannot be identified on CT [33]; CT cisternography may be reserved for cases where these have failed to identify a source. Intrathecal perioperative fluorescein can be utilised in cases where all available imaging modalities have been exhausted [30].…”
Section: Cerebrospinal Fluid Rhinorrhoeamentioning
confidence: 99%
“…The extracranial approach, such as the transnasal endoscopic surgical repair, has proved to be surgical interventions with minimal complications and a high success rate. 1,7 Surgical repair by Craniotomy was performed in the past, with a 60-80% success rate. Whereas open surgical repair requires a wide coronal incision with a high risk of permanent anosmia as a major complication.…”
Section: Introductionmentioning
confidence: 99%